Full-thickness burn scar treatment using a combination of microneedling and platelet-rich plasma in animal model - Santos, Kamylla Caroline; dos Santos, Benedito Matheus; Ribeiro, Maisa; de Miranda Moraes, Júlia; Cagnini, Didier Quevedo [UNESP]; Liebano, Richard Eloin; Araujo, Gustavo Henrique Marques (Elsevier, 2024)
Microneedling (MA) and platelet-rich plasma (PRP) therapies have shown potential for enhancing scar repair through collagen production and growth factor release, yet their effects on full-thickness burn scars remain underexplored. This study evaluated the impact of MA, PRP, and combined MA + PRP treatments on scar healing in a rat model of full-thickness burns. Fifty adult rats were divided into four groups: control, MA, PRP, and MA + PRP. Treatments were administered 21 days post-burn, and animals were evaluated at 14- and 21-days post-treatment. Macroscopic, histopathological, and morphometric analyses were performed to assess epithelialization, extracellular matrix (ECM) organization, and collagen deposition. The combination of MA + PRP demonstrated superior outcomes, showing enhanced ECM organization, significant collagen deposition, increased angiogenesis, and an improved inflammatory profile with mononuclear cell infiltration. Morphometric analysis confirmed a substantial increase in collagen content, particularly in the MA + PRP group, supporting improved tissue remodeling and scar maturation. These findings suggest that combined MA + PRP therapy may be a promising approach for promoting effective and accelerated burn scar healing. Further research is warranted to optimize protocols for clinical application.
Keywords: Burn scar repair; Collagen deposition; Extracellular matrix (ECM) remodeling; Microneedling (MA); Platelet-rich plasma (PRP)